2023
DOI: 10.3171/2022.10.focus22603
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic alignment outcomes after the single-position prone transpsoas approach: a multi-institutional retrospective review of 363 cases

Abstract: OBJECTIVE The aim of this paper was to evaluate the changes in radiographic spinopelvic parameters in a large cohort of patients undergoing the prone transpsoas approach to the lumbar spine. METHODS A multicenter retrospective observational cohort study was performed for all patients who underwent lateral lumber interbody fusion via the single-position prone transpsoas (PTP) approach. Spinopelvic parameters from preoperative and first upright postoperative radiographs were collected, including lumbar lordosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…12,19 Previous studies have shown that the PTP approach has significant improvement in operative efficiency and sagittal alignment compared with standard LLIF. 12,20 However, none of these studies focused on the clinical outcomes of the PTP approach in a large patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…12,19 Previous studies have shown that the PTP approach has significant improvement in operative efficiency and sagittal alignment compared with standard LLIF. 12,20 However, none of these studies focused on the clinical outcomes of the PTP approach in a large patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurg Focus. 2023;54 [1]:E3) is interesting and significant to us. In the authors' study, the lateral lumbar interbody fusion (LLIF) procedure was performed via the prone transpsoas (PTP) approach in 363 cases.…”
Section: Does the Prone Transpsoas Approach Affect Llif Outcomes?mentioning
confidence: 93%
“…TO THE EDITOR: The article by Diaz-Aguilar et al 1 (Diaz-Aguilar L, Stone LE, Soliman MAR, et al Radiographic alignment outcomes after the single-position prone transpsoas approach: a multi-institutional retrospective review of 363 cases. Neurosurg Focus.…”
Section: Does the Prone Transpsoas Approach Affect Llif Outcomes?mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial case series of prone LIF have demonstrated safety and efficacy with potentially shorter surgical times and improved segmental lordosis [18 , [25] , [26] , [27] , [28] , [29] , [30] . Patel et al.…”
Section: Introductionmentioning
confidence: 99%